THE INFLUENCE OF INCOME AND FINANCIAL LITERACY ON INVESTMENT DECISIONS WITH FINANCIAL BEHAVIOR AS A MODERATING VARIABLE (STUDY OF GENERATION Z IN SURABAYA CITY) - Ramdhania, Nur Alimah; Sriyono, Sriyono; Prapanca, Detak (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to determine, (1) the effect of income on investment decisions, (2) the effect of financial literacy on investment decisions, (3) the effect of income on investment decisions with financial behavior as a moderating variable, and (4) the effect of financial literacy on investment decisions with financial behavior as a moderating variable. This study uses purposive sampling technique, with data collection using a questionnaire. The sample used in this study was 100 out of 142 respondents. The results showed that income has a significant effect on investment decisions. Financial literacy has a significant effect on investment decisions. Financial behavior moderates the effect of income on investment decisions, financial behavior acts as pseudo moderation. Financial behavior does not moderate the effect of financial literacy on investment decisions, financial behavior as a predictor.